Integration of innovation development and implementation processes in defence industry according to a demand — supply format - A. I. Shinkevich; D. V. Kharitonov (Вестник университета)
The purpose of this study is to investigate the development and implementation processes of defence innovation in a demand – supply format. The main research methods are the dialectical and systematic approach, the method of formalisation and modelling, logical-functional and logical-structural analysis. The result of the study is the design of a lifecycle matrix for the development and implementation phases of defence innovation that visualises the objectives, functions, indicators, key deliverables by phase and stage of the innovation lifecycle. The matrix is intended for managers as a tool to help formulate the functions of the participants in the innovation process and to monitor and analyse problem areas in the innovation system. A business model of the innovation system of the defense complex in the demand – supply format is proposed, including elements that create supply and demand for innovative products, implement mediation mechanisms between participants that generate supply and demand. The results obtained are aimed at developing a methodology for organising and managing the development and implementation of innovations in the defence industry and can be used by authorities in the innovation policy formation, in developing and improving the programmes for the defence industry development in Russia.